Dampak Teknologi Informasi Berbasis Artificial Intelligence terhadap Kepuasan dan Loyalitas Wisatawan: Tinjauan Systematic Literature Review - Fahrurozi, Slamet Kurniawan; Epin Andrian, Dimas Pamilih (Lembaga Yasin AlSys, 2025)
This study aims to analyze the impact of Artificial Intelligence (AI)-based information technology on tourist satisfaction and loyalty through a systematic literature review method. Following the PRISMA guidelines, researchers conducted a literature search in the ScienceDirect and SpringerLink databases using keywords such as